Comparing the Anxiety of Children When Entering and Leaving the Operating Room with and without the Presence of Parents - navid kalani (Journal of Global Pharma Technology, 2017)
Surgery is one of the most frightening therapeutic procedures that can in children so that it can prevent to achieve therapeutic purposes and its controlling is very important. This study was conducted to compare the children's anxiety when entering and leaving the operating room with and without the presence of their parents.Methods: In this clinical trial study, 38 children aged 3 to 9 years who underwent tonsillectomy surgery were randomly assigned to experimental and control groups. In the experimental group, parents were with children during induction of anesthesia. The anxiety of children was measured based on the m-ypas scale. Finally, the data were analyzed using descriptive statistics, chi-square and Fisher test by Spss 21 software.Results: Mann-Whitney test showed that there is difference between experimental and control groups of children in terms of anxiety scales of children including emotional expressivity, vocalization, State Apparent Stimulated, and use of parents (p-value <0.05, Table 2), but there is no difference between two experimental and control groups in terms of scale of activity (p-value>0.05). Additionally, there is difference between them in terms of anxiety (p-value> 0.05). The mean of the anxiety in the experimental (43.68) reduced compared to control group (60.09). This means that the presence of parents has impact on level of anxiety during induction of anesthesia on 2 to 7 years old children undergoing surgery.Conclusion: The results showed that parental presence has impact on anxiety during induction of anesthesia on 3 to 7 years old children undergoing surgery. Keywords: Anxiety, Parents, Children.